Implementation of the Improved Active Frequency Drift Anti-Islanding Method into the Three-Phase AC/DC Converter with the LCL Grid Filter - Krzysztof Dmitruk; Andrzej Sikorski (Energies, 2022)
The article presents a modified standard Active Frequency Drift (AFD) method used to detect unintentional island operation in converters generating electricity from renewable energy sources to the power grid. The primary aim of each of the island operation detection methods is the possibility of shortening the energising of a separate part of the power grid. The proposed method eliminates fragments of the reference current signal when it reaches a constant value for a particular time. This part of the signal is replaced with the hyperbolic sine function. It allows reducing the value of Total Harmonic Distortions (THD) while maintaining the same effectiveness of island operation detection. The article contains a detailed description of the newly proposed type of disturbance generation. The proposed solution is verified by conducting simulation and laboratory tests. The possibility of shortening the island operation detection time is proven by increasing the maximum distortion introduced into the current without exceeding the permissible THD limit for converters connected to the power grid.